2017
DOI: 10.1103/physrevlett.119.141803
|View full text |Cite
|
Sign up to set email alerts
|

New Constraints on Light Vectors Coupled to Anomalous Currents

Abstract: We derive new constraints on light vectors coupled to standard model (SM) fermions, when the corresponding SM current is broken by the chiral anomaly. The cancellation of the anomaly by heavy fermions results, in the low-energy theory, in Wess-Zumino-type interactions between the new vector and the SM gauge bosons. These interactions are determined by the requirement that the heavy sector preserves the SM gauge groups and lead to (energy/vector mass)^{2} enhanced rates for processes involving the longitudinal … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
161
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 152 publications
(165 citation statements)
references
References 59 publications
4
161
0
Order By: Relevance
“…One can also wonder how a direct coupling of the vector to the bs current in Q (4) and Q (4) is possible. Recent studies have shown that these interactions do indeed arise in models where a light V couples to quark currents that are not conserved when the SM mass terms and/or quantum anomaly effects are taken into account [35,36]. Models with direct flavour-universal couplings of V to the axial-vector current of quarks tend to develop Q (4) at one loop, while models with a coupling of V to any linear combination of lepton and baryon currents other than B − L induce Q (4) at the two-loop level.…”
Section: Jhep03(2018)188mentioning
confidence: 99%
See 3 more Smart Citations
“…One can also wonder how a direct coupling of the vector to the bs current in Q (4) and Q (4) is possible. Recent studies have shown that these interactions do indeed arise in models where a light V couples to quark currents that are not conserved when the SM mass terms and/or quantum anomaly effects are taken into account [35,36]. Models with direct flavour-universal couplings of V to the axial-vector current of quarks tend to develop Q (4) at one loop, while models with a coupling of V to any linear combination of lepton and baryon currents other than B − L induce Q (4) at the two-loop level.…”
Section: Jhep03(2018)188mentioning
confidence: 99%
“…For Q (4) we assume that the interaction is induced by the couplings of the vector to anomalous currents in which case the coupling is two-loop suppressed [35] and we have…”
Section: Jhep03(2018)188mentioning
confidence: 99%
See 2 more Smart Citations
“…The fourth topology, denoted as 1D, is Z → A 0 γ → ðχχÞγ. It can come from the Wess-Zumino term ϵ μνρσ A 0 μ B ν ∂ ρ B σ when the dark photons couple to anomalous currents [130,131,131]. After integrating by parts, the longitudinal part of A 0 has interaction similar to the topology 1C; thus, the limit on the exotic Zdecay BR is similar to 1C.…”
Section: Exotic Decaysmentioning
confidence: 99%